Erythrocyte differentiation during the metamorphic hemoglobin switch of Rana catesbeiana. - Dorn, A R (1982)
Anurans (frogs and toads) switch from tadpole to adult hemoglobin synthesis during metamorphosis. A number of workers have attempted to determine whether tadpole and adult Hb types are expressed in the same or different erythroid cells during the switch. If the different Hb types are found in different cells during the transition, the switch in globin gene expression occurs at an early stage of cellular differentiation. Previous studies, in which immunocytochemical techniques were used to approach this question, are in conflict in regard to the metamorphic Hb switch of the North American bullfrog Rana catesbeiana. We have purified newly differentiating erythroid cells from the blood of metamorphosing tadpoles by using Percoll gradients. These new cells have an immature morphology, are very active in the synthesis of adult Hb, and contain no detectable tadpole Hb. The tadpole cells have no detectable adult Hb, are synthetically inactive, increase in density during the switch, and are then cleared from the circulation. Thus, only adult Hb expression is detected in newly differentiating erythroid cells during metamorphosis.